POTENSI DAN SKENARIO PENGEMBANGAN WISATA JEMBATAN PELANGI DI KABUPATEN SUPIORI PAPUA (Potensial and Development Scenarios the rainbow bridge tourism in Supiori Regency) - Mahmud Mahmud; Filda Listy Ayu; Matheus Beljai (Forestry Study Program University Of Mataram, 2023)
Tourism is one of the sectors that an important contribution to national and regional economic growth. The purpose of this study to assessment potential tourist attraction objects and development scenarios for the rainbow bridge in Sorendiweri Village. The potential assessment uses the tourist attraction guidelines issued by the Directorate General of Forest Protection and Nature Conservation while the development analysis uses an analysis with the community based ecotourism development (CBED) model. The results showed that the rainbow bridge has a potential tourist attraction object of 2,545 (good). Communities and tourists regarding the development of objects and tourist attractions of the Rainbow Bridge perceive and accept and agree. Development scenarios so that rainbow bridge tourism is better known by the general public, both domestic and foreign tourists, including: adventure tourism in mangrove forest areas, identification of flora and fauna, visitor management, making tour packages, fulfillment and maintenance of infrastructure. The active role of the community and tourists greatly influences the existence of potential and future tourist objects.